PENGGUNAAN METODE KOMPOSTING UNTUK MENGOLAH LIMBAH HOTEL MENJADI PUPUK ORGANIK - Tyas, Dyah Wahyuning (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2016)
Tourism has become an industry with the highest growth. It is recognized by the government so that the government set out to develop the tourism. Sleman District Government understand the new paradigm in the approach of community-based tourism, so that the government was actively encouraging the community to take a role in the development of tourism in accordance with the existing potential in rural area. Recognizing the potential of Nganggring located on the slopes of Mount Merapi, which previously has been a tourist village that is developing but the damage occurred after the eruption of the volcano it is necessary redevelopment to make the villages that will be visited by tourists so that the local economy will be recovering back. This research is a qualitative research, is research that uses natural background for the purpose of interpreting the phenomenon happened and was done by involving the various methods that exist and to determine the development strategy. Based on the research results of SWOT analysis concluded strategy of development of Nganggring rural Tourism is objects and attractions geared towards creating efforts for long-stay travelers, creating a varied tourist attractions. Strategy to increase potential market directed to establish communication with the Tourism Rural Forum to build an integrated campaign. Development Program of rural tourism after the eruption of Merapi aims to improve social welfare. Keywords: Rural village, eruption, social welfare